Pengaruh Penambahan Pembenah Tanah dari Daun dan Akar Tanaman Eceng gondok (Eichhornia crassipes Solm.) terhadap Kapasitas lapang Tanah Pasir dan Tanah Liat serta Pertumbuhan Kacang Hijau (Vigna radiata L.) - Marlina, iis; Izzati, Munifatul; Saptiningsih, Endang (Jurnal Akademika Biologi, 2013)
Soil conditioner is materials that added to the soil.Â  Soil conditioner capable to improve soil structure, water holding capacity and infiltration. The aims of this research is to study the effect soil conditioner on the field capacity and growth of green peas that were planted in sandy and clay soil. The soil conditioner used in this research is consisted of two different species of aquatic plants, leaf and root E.crassipes. It is treatment was replicated 3 time. Sandy soil (T1) and clay soil (T2) without soil conditioner were served as controls. T1P1 (Sandy soil+soil conditioner leaf E.crassipes) T1P2 (Sandy soil+soil conditioner root E.crassipes) T2P1 (clay soil+soil conditioner leaf E.crassipes) T2P2 (clay soil+ soil conditioner root E.crassipes). Ratio of soil and soil conditioner is 75%:25%. Result indicated that addition of leaf and root E.crassipes conditioner significanly increased field capacity, both in sandy and clay soil. The controls soil or without soil conditioner field capacity is 12,20%. Increased field capacity by leaf E.crassipes is 18,56 % and root E.crassipes 16,60%.Â Key words: soil conditioner, eichhornia crassipes, field capacity, growth.